TRANSFORMATION OF ELEMENTARY EDUCATION MANAGEMENT: TOWARD ENHANCED LEARNING QUALITY AND STUDENT ACHIEVEMENT - Putu Artawan (Adisam Publisher, 2024)
In response to the dynamic landscape of the 21st century, elementary education management is undergoing a transformative journey focused on enhancing learning quality and elevating student achievement. This paper delves into a comprehensive exploration of strategies designed to meet the evolving demands of education in the digital age. The integration of cutting-edge educational technology, the development of a skills-based curriculum, the continuous enhancement of teacher competency, and the implementation of robust student support programs collectively shape the trajectory of this transformation. This transformative journey is intricately woven into the fabric of addressing the challenges posed by rapid technological growth and the shifting landscape of global demands. Emphasizing the need for a dynamic learning environment, the discussion navigates through the nuances of project-based learning methodologies and the integral role of parental involvement. The resultant framework is not merely an adaptation to change but a proactive and strategic approach to equip students with the skills, competencies, and adaptability required for success in the 21st century. By investing in these transformative initiatives, the educational landscape transcends traditional boundaries. It prepares students for the intricacies of the digital age and instills a profound love for learning that extends far beyond the confines of the classroom. This abstract encapsulates the essence of a holistic and forward-thinking approach to elementary education management, outlining a path that aligns with the broader goals of educational excellence and societal progress.